2002
DOI: 10.1111/1469-8986.3960747
|View full text |Cite
|
Sign up to set email alerts
|

Slow event‐related brain activity of aphasic patients and controls in word comprehension and rhyming tasks

Abstract: Slow event-related potentials (ERP) were examined in healthy and aphasic subjects in two-stimulus designs comprising a word comprehension and a rhyming task. Aphasics, though selected to perform above chance level, made significantly more errors and responded more slowly than controls, although canonical correlations did not indicate a statistical relationship between performance measures and ERP amplitudes. A discriminant analysis of ERP amplitudes distinguished the groups for the slow wave (SW; 0.5-1.0 s pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Asterisks indicate significant post hoc tests. patients in linguistic tasks, since they made more errors and were on average slower than controls (other studies confirmed a general decrease in aphasics' behavioral efficiency, Cohen et al, 2001;Dobel et al, 2002). Thus, in the patients, the deficit of central CNV was neither lateralized nor taskspecific.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Asterisks indicate significant post hoc tests. patients in linguistic tasks, since they made more errors and were on average slower than controls (other studies confirmed a general decrease in aphasics' behavioral efficiency, Cohen et al, 2001;Dobel et al, 2002). Thus, in the patients, the deficit of central CNV was neither lateralized nor taskspecific.…”
Section: Discussionmentioning
confidence: 83%
“…A number of recent ERP studies found significant differences in linguistic processing (lexical, semantic, and syntactic) between aphasics and controls (Friederici et al, 1999;Hagoort et al, 1996;Swaab et al, 1997). Another set of studies used electrophysiological methods to locate linguistic activation in aphasics: some studies pointed to greater activation of right hemisphere in aphasics (Moore, 1986;Selinger et al, 1989;Thomas et al, 1997), but there is also evidence of left frontal (Cohen et al, 2001;Thomas et al, 1997) and temporal (Dobel et al, 2002) cortex activation in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The first window was defined to examine early effects in the time range of the N1, P2, and N2, which have been reported to reflect specific lexical and semantic processes (Pulvermüller, Hummel, & Härle, 2001; Pulvermüller et al, 1995; Pulvermüller, Lutzenberger, & Preissl, 1999), the second window targeted the time range of the N400 component, which is kown to reflect semantic processing (Hagoort et al, 1996; Kutas & Federmeier, 2000), and the third window was analyzed to obtain possible clues about dynamics in late positive shifts or the CNV. The CNV has recently been found to be an indicator of language processes in aphasics (Dobel et al, 2001, 2002). The P300 and P600 components, which have been reported to reveal specific dynamics in patients with basal ganglia dysfunction (Frisch, Kotz, von Cramon, & Friederici, 2003; Pulvermüller, Lutzenberger, Müller, Mohr, & Birbaumer, 1996), were thought to contribute to all three windows, but to be best captured by the second window (see also Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…(c) A late P300‐like positivity, which can reveal syntactic processes (Hagoort, Brown, & Groothusen, 1993; Osterhout & Holcomb, 1992), was attenuated in agrammatic aphasia, although the P300 elicited in a standard oddball task in these patients resembled that in normal controls (Hagoort, Wassenaar, & Brown, 2003; Hagoort et al, 1996). (d) The equally late contingent negative variation (CNV) was recently reported to relate to altered lexical and phonological processes in aphasics (Dobel et al, 2001, 2002). In sum, all of these earlier studies documented a reduction or modification of language‐evoked brain responses in neurological patients suffering from an organic language deficit.…”
mentioning
confidence: 99%
“…In studies with dyslexic readers the CNV did not find much attention. However, one study did find a reduced CNV in reading impaired adolescents (McPherson, Ackerman, Holcomb, & Dykman, 1998) and reduced CNVs were also found in cases of acquired dyslexia (Cohen et al, 2001;Dobel et al, 2002). Further, in a large sample of unimpaired English readers the CNV was found to increase with age and reading competence (Grossi, Coch, Coffey-Corina, Holcomb, & Neville, 2001).…”
Section: Discussionmentioning
confidence: 97%